2019
DOI: 10.1016/j.amepre.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immunization in the U.S.: A Nationwide Retrospective Cohort Study

Abstract: Introduction: At present, pregnant women in the U.S. are recommended to receive tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) and influenza vaccines. This study assessed maternal coverage of these 2 vaccinations. Methods: Data for this retrospective cohort study were extracted from 2 large administrative claims databases, the MarketScan Commercial and Multi-State Medicaid Databases, for 2009−2017 and analyzed in 2018. Women aged 15−44 years on the date of pregnancy end were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…[30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain. 36 The main characteristics of the included studies are summarized in Tables 1 and S2.…”
Section: Re Sultsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain. 36 The main characteristics of the included studies are summarized in Tables 1 and S2.…”
Section: Re Sultsmentioning
confidence: 99%
“…For example, the 2016 vaccine rates for tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine administration to adults aged 18 years and older in the United States using the interactive AdultVaxView system 34 shows significant regional variations in vaccine uptake, with Vermont and Minnesota having the highest vaccination rates at 54.2% and 51.7%, respectively, and Mississippi having the lowest vaccination rate at 23.2%. A retrospective cohort study 35 examining Tdap and influenza vaccinations during pregnancy found that in 2017, rates of these vaccinations ranged from 31.4% to 56.3% and 17.5% to 31.3%, respectively. Hill et al 36 found that rates of recommended pediatric vaccinations by age 24 months from 2017 to 2019 were 35.7% for influenza vaccine in uninsured children and 69.6% for those with private insurance coverage and were 84.7% and 95.9%, respectively, for Tdap.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…For example, health care professional electronic record automated alerts and the provision of maternal vaccinations by midwives at antenatal appointments significantly increase uptake of a pregnancy dose of acellular pertussis vaccine [26]. However, antenatal vaccine uptake is suboptimal in many countries [22][23][24][27][28][29].…”
Section: Introductionmentioning
confidence: 99%